PENYELESAIAN PERSOALAN TRANSPORTASI FUZZY COST MENGGUNAKAN PENDEKATAN BASIS TREE DAN METODE NWC-STEPPING STONE - Ary, Maxsi; Herman, Asep (Jurnal Techno Nusa Mandiri, 2013)
<span style="display: inline !important; float: none; background-color: transparent; color: #000000; font-family: Verdana,Arial,Helvetica,sans-serif; font-size: 11.2px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">The issue of transportation is a linier program. Practically, variables of transportation problems may vary that emerges more than single. Fuzzy cost idea in transportation problems is required. The application of basis tree approach and NWC-Stepping Stone method is used to determine a minimum cost of purchase and delivery of commodity occurred for some suppliers. The company can do a cost-saving and be more effective in determining goods purchase from the supplier. The method used is quantitative experiments, the primary data on the PPIC and purchasing. The results of calculation of basis tree approach on PT Busana Cemerlang Garment Industry are the feasible shipping cost 63993.55, the optimistic shipping cost 62073.74, and the pessimistic shipping cost 65913.35. The results of NWC-Stepping Stone method is 63993.55. There is a deviation 6480 with the calculation of purchase order (PO).